Desmoplastic Reaction, Immune Cell Response, and Prognosis in Colorectal Cancer - Akimoto, Naohiko; Väyrynen, Juha P.; Zhao, Melissa; Ugai, Tomotaka; Fujiyoshi, Kenji; Borowsky, Jennifer; Zhong, Rong; Haruki, Koichiro; Arima, Kota; Lau, Mai Chan; Kishikawa, Junko; Twombly, Tyler S.; et al. (Frontiers in Immunology, 2022)
Background The relationships between tumor stromal features (such as desmoplastic reaction, myxoid stroma, and keloid-like collagen bundles) and immune cells in the colorectal carcinoma microenvironment have not yet been fully characterized. Methods In 908 tumors with available tissue among 4,465 incident colorectal adenocarcinoma cases in two prospective cohort studies, we examined desmoplastic reaction, myxoid stroma, and keloid-like collagen bundles. We conducted multiplex immunofluorescence for T cells [CD3, CD4, CD8, CD45RO (PTPRC), and FOXP3] and for macrophages [CD68, CD86, IRF5, MAF, and MRC1 (CD206)]. We used the inverse probability weighting method and the 4,465 incident cancer cases to adjust for selection bias. Results Immature desmoplastic reaction was associated with lower densities of intraepithelial CD3+CD8+CD45RO+ cells [multivariable odds ratio (OR) for the highest (vs. lowest) density category, 0.43; 95% confidence interval (CI), 0.29–0.62; Ptrend <0.0001] and stromal M1-like macrophages [the corresponding OR, 0.44; 95% CI, 0.28–0.70; Ptrend = 0.0011]. Similar relations were observed for myxoid stroma [intraepithelial CD3+CD8+CD45RO+ cells (Ptrend <0.0001) and stromal M1-like macrophages (Ptrend = 0.0007)] and for keloid-like collagen bundles (Ptrend <0.0001 for intraepithelial CD3+CD8+CD45RO+ cells). In colorectal cancer-specific survival analyses, multivariable-adjusted hazard ratios (with 95% confidence intervals) were 0.32 (0.23–0.44; Ptrend <0.0001) for mature (vs. immature) desmoplastic reaction, 0.25 (0.16–0.39; Ptrend <0.0001) for absent (vs. marked) myxoid stroma, and 0.12 (0.05–0.28; Ptrend <0.0001) for absent (vs. marked) keloid-like collagen bundles. Conclusions Immature desmoplastic reaction and myxoid stroma were associated with lower densities of tumor intraepithelial memory cytotoxic T cells and stromal M1-like macrophages, likely reflecting interactions between tumor, immune, and stromal cells in the colorectal tumor microenvironment.